A High Percentage of NSCLC With Germline CHEK2 Mutation Harbors Actionable Driver Alterations: Survey of a Cancer Genomic Database and Review of Literature - Shannon S. Zhang, MD; Jessica K. Lee, MSc; Hanna Tukachinsky, PhD; Alexa B. Schrock, PhD; Misako Nagasaka, MD, PhD; Sai-Hong Ignatius Ou, MD, PhD (JTO Clinical and Research Reports, 2022)
Introduction: Germline CHEK2 mutations are rare and have not been associated with increased risk of NSCLC. Methods: We identified two sequential primary NSCLCs harboring distinct actionable driver alterations (EGFR E746 _S752 delinsV and CD74-ROS1) in a patient with NSCLC with a novel germline CHEK2 mutation S5fs∗54 (c.14_20delCGGATGT). We queried a genomic database of NSCLC samples profiled by plasma next-generation sequencing (Foundation Medicine Inc.) and performed a literature search of germline CHEK2 mutations in NSCLC. Results: Of 6101 patients with unique NSCLC profiled by plasma next-generation sequencing, 53 cases (0.87%) of germline CHEK2 mutation were identified (male-to-female ratio, 49%:51%; median age = 75 y). The median allele frequency of CHEK2 was 49% (interquartile range: 49%–51%). Ten unique CHEK2 germline mutations were identified. Literature review identified 15 additional cases of germline CHEK2 mutations in NSCLC. Overall, a total of 70 CHEK2 germline mutations (21 unique CHEK2 alterations) were identified. Among these 70 CHEK2 germline mutations, 54.3% were amino acid substitutions (point mutation), 40.0% were frameshift mutations, and 5.7% were splice site mutations. Of these 70 total cases assessed, 29 (41.4%) potentially actionable driver alterations were identified with KRAS G12C mutation (27.6%) being the most common and KRAS G12A/C/D/R/S/V mutations together constituting 51.7% of these driver mutations. Conclusions: Germline CHEK2 mutations are rare in NSCLC. A large proportion of these cases harbor actionable driver alterations. The relationship between germline CHEK2 mutations and actionable driver alterations in NSCLC may be worth further investigation.